2017
DOI: 10.1002/2016ja023591
|View full text |Cite
|
Sign up to set email alerts
|

The transient topside layer and associated current sheet in the ionosphere of Mars

Abstract: Radar soundings from the Mars Advanced Radar for Subsurface and Ionosphere Sounding (MARSIS) instrument on board the Mars Express spacecraft have shown that transient layers exist in the dayside upper ionosphere of Mars. The most prominent of these features is a second layer at an altitude near 200 km, well above that of the main photoionization layer. While the general properties of this layer have been studied previously, the inner workings of this layer, and the mechanisms that drive it, are only now becomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
2
17
0
Order By: Relevance
“…It is not known whether topside layers exist in regions of stronger crustal fields, because the presence of electron cyclotron harmonics in the ionograms can hinder the visibility of the ionospheric traces at low frequency, including any potential topside layer. Concurrent measurements of topside layers by MARSIS onboard the MEX orbiter and by the in situ particle and field package onboard the MAVEN orbiter indicate localized increases in the in situ electron density and total ion density in the vicinity of the topside layers detected remotely by MARSIS (Kopf et al, ). These authors also found simultaneous magnetic field rotations and magnetic field dips, attributed to current sheets.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…It is not known whether topside layers exist in regions of stronger crustal fields, because the presence of electron cyclotron harmonics in the ionograms can hinder the visibility of the ionospheric traces at low frequency, including any potential topside layer. Concurrent measurements of topside layers by MARSIS onboard the MEX orbiter and by the in situ particle and field package onboard the MAVEN orbiter indicate localized increases in the in situ electron density and total ion density in the vicinity of the topside layers detected remotely by MARSIS (Kopf et al, ). These authors also found simultaneous magnetic field rotations and magnetic field dips, attributed to current sheets.…”
Section: Discussionmentioning
confidence: 98%
“…Kopf et al () have discovered the existence of transient topside layers above the main ionospheric peak, at typical altitudes 180–240 km on the dayside, with an occurrence rate decreasing when going from the subsolar region to the terminator (from 60% to 5% of observation time). The topside layers are found mostly in regions of low crustal magnetic field strength (e.g., Kim et al, ; Kopf et al, ). It is not known whether topside layers exist in regions of stronger crustal fields, because the presence of electron cyclotron harmonics in the ionograms can hinder the visibility of the ionospheric traces at low frequency, including any potential topside layer.…”
Section: Discussionmentioning
confidence: 99%
“…In this case, the relative velocity between the Martian ionosphere and the cometary coma could cause these extra topside layers as in, for example, Kopf et al (2017). In this case, the relative velocity between the Martian ionosphere and the cometary coma could cause these extra topside layers as in, for example, Kopf et al (2017).…”
Section: Plasma Instabilitiesmentioning
confidence: 97%
“…Figure 4 shows four MARSIS-AIS topside electron density profiles (blue lines, Panels a-d) within less than 8 min and their corresponding NeMars profiles (black dashed lines). Kopf et al (2017) recently suggested that these extra layers are related to local current sheets in the upper Martian ionosphere, which could be related to Kelvin-Helmholtz instabilities, magnetic flux ropes, magnetic reconnection, or solar wind magnetic field rotations. In addition, the corresponding ionograms from which the profiles were retrieved are shown in Panels e-h.…”
Section: Ionosphere Between 130 and 350 Kmmentioning
confidence: 99%
“…Ionospheric structure above the main peak layer at Mars was initially dismissed as noise in the radio signal (Kliore, 1992). However, in the past several decades of accumulated ionospheric observations, the occurrence of topside plasma layers in observations has persisted (Acuña et al, 2001;Andrews et al, 2014;Diéval et al, 2015;Eastwood et al, 2008;Fillingim et al, 2012;Fox & Yeager, 2006;Gurnett et al, 2005Gurnett et al, , 2008Kliore, 1992;Kopf et al, 2008Kopf et al, , 2017Luhmann, 1986;Modolo et al, 2005;Morgan et al, 2008;Riousset et al, 2014;Shinagawa & Cravens, 1992;Terada et al, 2002;Wang et al, 2009; Figure 1. An MGS radio occultation ionospheric profile (ID 0353F17B.EDS, measured on 18 December 2000) is shown in black with uncertainties in gray horizontal bars.…”
Section: Introductionmentioning
confidence: 99%